Corporate green innovation: The influence of ESG information disclosure - Lei Ruan; Liwen Yang; Kunyang Dong (Journal of Innovation & Knowledge)
Environmental, Social, and Governance (ESG), a key concept in sustainable development, plays a critical role in shaping corporate green economic activities. This study investigated the effect of ESG information disclosure on corporate green innovation using data from Chinese A-share listed companies from 2013 to 2022. The findings revealed that ESG information disclosure significantly fosters corporate green innovation and the results remain robust across various robustness checks and endogeneity tests. The heterogeneity analysis indicated that the positive effect of ESG information disclosure on corporate green innovation is more pronounced among state-owned enterprises, firms located in the eastern region, and companies operating in non-heavily polluting industries. Furthermore, mechanism analysis suggested that ESG information disclosure influences corporate green innovation through two primary channels: easing financing constraints and attracting the attention of analysts. However, this study acknowledged the limitations of the mechanism analysis. Future research should aim to integrate insights from related disciplines to further explore the mechanisms by which ESG information disclosure affects corporate green innovation from a more comprehensive perspective.